2011
DOI: 10.1111/j.1600-0412.2011.01147.x
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal diagnosis of placenta accreta leads to reduced blood loss

Abstract: Antenatal diagnosis of placenta accreta may reduce peripartum blood loss and the need for blood transfusion. Women with antenatal diagnosis more often have placenta previa and history of previous cesarean section, and the clinical diagnosis is more often placenta percreta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
153
2
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(170 citation statements)
references
References 26 publications
8
153
2
7
Order By: Relevance
“…Morbidly adherent placenta is one of the most devastating complications in pregnancy [10]. It is characterized by the attachment of placental villi directly to the myometrium, sometimes invading deeper into the uterine wall or surrounding organs.…”
Section: Discussionmentioning
confidence: 99%
“…Morbidly adherent placenta is one of the most devastating complications in pregnancy [10]. It is characterized by the attachment of placental villi directly to the myometrium, sometimes invading deeper into the uterine wall or surrounding organs.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, parity and the number of previous cesarean sections were significantly high among women who had difficult placental delivery, considerable intraoperative blood loss, who required emergency hysterectomy to control bleeding. Wright et al (29) found that 41.7% of women with a known placenta accreta had a blood loss of ≥5000 mL, and, although Wright et al (29) concluded that there was no significant relation between parity, number of previous cesarean deliveries, degree of placental invasion, and massive blood loss, Tikkanen et al (30) found that the risk factors of placenta accreta included parity, cesarean section, and placenta previa. In addition, Guleria et al (31) concluded that the risk factors of abnormal invasive placentation (AIP) were placenta previa and a past history of cesarean delivery, and Thia et al (32) concluded that the depth of invasion in MAP is increased with multiple previous surgeries or excessive curettage or infection causing defective decidua basalis.…”
Section: Discussionmentioning
confidence: 99%
“…Warshak et al (33) concluded that antenatal detection of placenta accreta was associated with a significant decrease in maternal hemorrhage. In addition, Tikkanen et al (30) concluded that the diagnosis of placenta accreta may significantly reduce peripartum blood loss, and Chantraine et al (34) concluded that the prenatal diagnosis of AIP reduces morbidity and undiagnosed cases of AIP led to more emergency hysterectomies (33,30,34). Eller et al (35) concluded that planned cesarean hysterectomy and preoperative ureteric stents were associated with reduced maternal morbidity in MAP.…”
Section: Discussionmentioning
confidence: 99%
“…[27,28] Como lo documentado en los reportes de caso revisados [2,4,10,14-16,18-19,22] la sospecha diagnostica de esta patología se tiene por medio de la ecografía, pudiendo coexistir en una misma paciente distintos grados de acretismo. [29] El uso de ecografía transabdominal puede encontrar solución de continuidad en el miometrio en el 35% de las mujeres con espesor <2,0 mm.…”
Section: Presentación Del Casounclassified